Public Goods, Signaling, and Norms of Conscientious Leadership - J. Atsu Amegashie (Center for Economic Studies and ifo Institute (CESifo), 2016)
I study a sequential-move public goods game based on the notion that leadership comes with an obligation; conscientious leadership. Provision by the leader of an amount of the public good below a minimum imposes a psychological cost on the follower which increases his unit cost of contribution. The leader has private information about his type and his cost of contributing to the public good. The model combines a follower's concern for fairness and informational signaling about conscientious leadership. I find that, under certain conditions, the follower's equilibrium contribution is an increasing or non-monotonic function of the leader's equilibrium contribution. The non-monotonicity result is consistent with evidence in a recent field experiment (Jack and Recalde, J. Public Econ, 2015) but cannot be obtained in previous theoretical models of voluntary public goods games that were based on only signaling information (i.e., about the quality of the public good or the return to contributions to the public good). Surprisingly, I find that, for this result to hold, the follower's distaste for non-conscientious leadership must be sufficiently low. I also find that the leader may not act conscientiously if he does not have an informational advantage to exploit.
Keywords: H00; H30; H50; 330; conscientious leadership; fairness; public good; signaling